Impact of three different daily doses of vitamin D3 supplementation in healthy schoolchildren and adolescents from North India: a single-blind prospective randomised clinical trial. Issue 5 (29th January 2019) - Marwaha, Raman K.; Garg, Mahendra K.; Sethuraman, Gomathy; Gupta, Nandita; Mithal, Ambrish; Dang, Navin; Kalaivani, Mani; Ashraf Ganie, Mohd; Narang, Archana; Arora, Preeti; Singh, Annie; Chadha, Aditi; et al.
Abstract: In India, there is a lack of information about the adequate daily dose of vitamin D3 supplementation in school children. Hence, we undertook this study to evaluate the adequacy and efficacy of different doses of vitamin D3 in schoolchildren. A total of 1008 vitamin D-deficient (VDD) children, aged 6–16 years with serum 25-hydroxyvitamin D (25(OH)D) levels <50nmol/l, were cluster randomised into three groups (A-344, B-341 and C-232) for supplementation (600, 1000 and 2000 IU daily) of vitamin D3 under supervision for 6 months. Of the 1008 subjects who completed the study, 938 (93 %) were compliant. Baseline and post-supplementation fasting blood and urine samples were evaluated for Ca, phosphates, alkaline phosphatase, 25(OH)D and parathormone and urine Ca:creatinine ratio. The mean age of the subjects was 11·7 (sd 2·4) years, and the overall mean baseline serum 25(OH)D level was 24·3 (SD 9·5)nmol/l. Post-supplementation rise in serum 25(OH)D in compliant group was maximum with 2000 IU (70·0 (SD 30·0)nmol/l), followed by 1000 IU (46·8 (SD 22·5)nmol/l) and 600 IU (36·5 (SD 18·5)nmol/l), and serum 25(OH)D levels of ≥50nmol/l were achieved in 71·5, 81·8 and 92·9 % by groups A, B and C, respectively. Secondary hyperparathyroidism decreased from 31·7 to 8·4 % post-supplementation. Two participants developed hypercalciuria, but none developed hypercalcaemia. Children with VDD benefit maximum with the daily supplementation of 2000 IU of vitamin D3 . Whether recommendations of 400 IU/d by Indian Council of Medical Research or 600 IU by Indian Academy of Pediatrics or Institute of Medicine would suffice to achieve vitamin D sufficiency in children with VDD remains debatable.